Incidence of acute respiratory infections and their associated pathogen distribution among residents in Shanghai, China: preliminary results from community-based surveillance in the 2023-2024 influenza season - Yilin Jia; Li Zhang; Yanxin Xie; Lipeng Hao; ChuChu Ye; Xinmei Zhou; Linghui Zhao; Bing Zhao; Yifeng Shen (International Journal of Infectious Diseases)
Objectives: This study aimed to assess the risk of acute respiratory infections across distinct age demographics, analyze factors associated with infection, and characterize respiratory pathogen epidemiology in the post-COVID-19 era. Methods: We conducted this longitudinal community-based surveillance study in Pudong New Area from November 2023 to January 2024. Questionnaires were designed to assess acute respiratory infection (ARI) incidence, and respiratory pathogens were detected among qualified patients with ARI. Pathogenic features were compared and analyzed among different age groups. Results: A total of 6698 participants were included and completed the study. The overall ARI incidence was 2.55 (95% CI 2.42-2.68) per 1000 person-days. The incidence of ARI progressively decreased with increasing age. The factors significantly associated with infection were sex, employment, and chronic conditions among participants who reported symptoms. Influenza virus, Haemophilus influenzae, human rhinovirus, and human coronavirus were the most commonly detected viruses. The positive distribution rate was similar among all age groups. The influenza virus trend maintained a prolonged peak period. Conclusions: The incidence of ARI exhibited a progressive decline with advancing age. Community-based surveillance identifies respiratory pathogen profiles during early or mild infections, complementing routine surveillance.